CRITICAL EPISTEMOLOGY IN ISLAMIC EDUCATION: STRATEGIES FOR DEALING WITH INSTANT RELIGIOUS AUTHORITIES ON SOCIAL MEDIA - Tsaabitah, Aliifatus; Hidayat, Adi; Aisi, Rohadatul; Sesmiarni, Zulfani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information technology and social media has transformed the patterns of religious knowledge dissemination, marked by the emergence of instant religious authority. While this phenomenon facilitates access to information, it also has the potential to produce shallow and unverified religious understanding, as well as to foster exclusive and intolerant attitudes among students. This study aims to examine the integration of critical epistemology in Islamic Religious Education (PAI) as a strategy to address this phenomenon. The research employs a qualitative approach using library research, involving the collection and analysis of relevant literature through content analysis techniques. The findings indicate that the application of critical epistemology emphasizing reflection, rationality, source analysis, and constructive skepticism can enhance students’ religious and digital literacy. This approach also promotes deeper and more contextual religious understanding, as well as moderate, open, and tolerant attitudes toward differences. Furthermore, the integration of critical epistemology requires adaptive curriculum development and the improvement of teachers’ competencies in critical-based learning. Therefore, critical epistemology serves as a strategic approach to strengthen the role of Islamic Religious Education as a filter against the flow of religious information in the digital era.